Tax shocks, sunspots and tax evasion - Francesco Busato; Bruno Chiarini; Enrico Marchetti (The Open Economics Journal, 2010)
This paper shows that an increase in corporate/labor/income tax rates may push an economy with tax evasion into an expansionary pattern, under increasing returns to scale. These effects would be reversed when the steady state is saddle-path stable. This model does not undertake a full identification. The interesting feature of our results is that fiscal policy in an economy with a significant underground sector may provide inadvisable outcomes. Thus, tax policies can generate counterproductive results in an economy characterized by existence of aggregate increasing returns to scale and underground activities.
Keywords: 330; dynamic general equilibrium models; fiscal policy; tax evasion and underground activities; indeterminacy and sunspots